1996
DOI: 10.1093/rheumatology/35.4.350
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Pituitary Function in Patients With Newly Diagnosed Rheumatoid Arthritis

Abstract: Hormonal dysfunction involving the hypothalamic-pituitary-adrenal (HPA) axis, prolactin (PRL) secretion and sex hormone status has been supposed to contribute to the development or persistence of rheumatoid arthritis (RA). In addition, a reduced number of glucocorticoid receptors on circulating lymphocytes has been found in patients with RA. However, so far most studies have been performed in pre-treated patients. A combined test for total anterior pituitary reserve was performed in 10 patients with newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 20 publications
4
47
2
Order By: Relevance
“…In patients with MS, the cortisol response to CRF differs depending on the disease status of the individual (Wei & Lightman, 1997). Similarly, in patients with RA, the cortisol response to challenge with releasing hormones is impaired in individuals with established disease (Gudbjornsson et al 1996), but not in newly diagnosed untreated RA patients (Templ et al 1996).…”
Section: Is the Hpa Axis Altered In Patients With Autoimmune Disease?mentioning
confidence: 99%
“…In patients with MS, the cortisol response to CRF differs depending on the disease status of the individual (Wei & Lightman, 1997). Similarly, in patients with RA, the cortisol response to challenge with releasing hormones is impaired in individuals with established disease (Gudbjornsson et al 1996), but not in newly diagnosed untreated RA patients (Templ et al 1996).…”
Section: Is the Hpa Axis Altered In Patients With Autoimmune Disease?mentioning
confidence: 99%
“…A significant decrease in serum concentrations of IGF-I as well as in pituitary GH mRNA content has been described in arthritic rats (5,6), indicating a decrease in pituitary GH secretion. In humans with rheumatoid arthritis, a significant decrease in GH and IGF-I secretion has also been described (7,8). We have recently observed that recombinant human GH (rhGH) administration to arthritic rats can ameliorate the decrease in IGF-I and BW and the increase in circulating IGF-binding proteins (9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature data have shown that, in comparison with controls, RA patients have, almost signi®cantly, reduced plasma IGF-I levels and clearly reduced plasma IGF-II and insulin-like growth factor-binding protein-3 levels which, however, are increased in synovial¯uid (28). Previous literature data have shown a blunted GH response after growth hormone-releasing hormone in RA patients when compared with controls, and this ®nding might be due to the increased IL-1 levels found in these patients which is known to stimulate somatostatin synthesis and release in rat hypothalamus (29). The reduced IGF-I levels found in our RA patients might not therefore be merely secondary to a chronic illness such as RA, but might be due to multiple factors such as a reduced activity of the GH±IGF-I axis and a passage of the peptide from the circulation to the synovial space (28).…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 73%